Use of concomitant variceal embolization and prophylactic antiplatelet/anticoagulative in transjugular intrahepatic portosystemic shunting: A retrospective study of 182 cirrhotic portal hypertension patients. Issue 49 (December 2017) - Tang, Yingmei; Zheng, Sheng; Yang, Jinhui; Bao, Weimin; Yang, Lihong; Li, Yingchun; Xu, Ying; Yang, Jing; Tong, Yuyun; Gao, Jinhang; Tang, Chengwei
Abstract : Abstract: Transjugular intrahepatic portosystemic shunting (TIPS) is an effective treatment modality for refractory variceal bleeding and ascites in patients with cirrhotic portal hypertension (CPH). Variceal rebleeding and shunt dysfunction are major post-TIPS morbidities. This study aimed to retrospectively evaluate the effectiveness and safety of use of concomitant variceal embolization and prophylactic antiplatelet/anticoagulative in patients with CPH undergoing TIPS. Between October 2006 and October 2011, 182 patients with CPH were retrospectively and consecutively hospitalized for elective TIPS with Fluency stenting. Concomitant variceal embolization was given after establishing the shunt. Subcutaneous heparin was given after TIPS and replaced by oral clopidogrel, aspirin, or warfarin for at least 6 months. Main outcome measures included shunt patency rate, recurrence of CPH (rebleeding and/or refractory ascites), hepatic encephalopathy (HE) frequency, and post-TIPS survival. The cumulative primary patency rate was 96%, 94%, 90%, 88%, and 88% at 6, 12, 24, 36, and 48 months, respectively. Shunt stenosis occurred in 16 (9%) patients, gastrointestinal (GI) rebleeding in 32 (17.5%) patients, recurrence of refractory ascites 44 (48%) patients, HE in 42 (23%) patients, and death in 36 (20%) patients during the follow-up period. Use of concomitant variceal embolization and prophylactic antiplatelet/anticoagulative was associated with a favorable shunt patency and a low risk of GI rebleeding.